2016
DOI: 10.1186/s12864-016-3286-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic differentiation among wild cyanophages despite widespread horizontal gene transfer

Abstract: BackgroundGenetic recombination is a driving force in genome evolution. Among viruses it has a dual role. For genomes with higher fitness, it maintains genome integrity in the face of high mutation rates. Conversely, for genomes with lower fitness, it provides immediate access to sequence space that cannot be reached by mutation alone. Understanding how recombination impacts the cohesion and dissolution of individual whole genomes within viral sequence space is poorly understood across double-stranded DNA bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 69 publications
3
108
1
Order By: Relevance
“…; Gregory et al . ) is generally consistent with the plausibility of KTW dynamics, but observations of complex, natural communities that may support or refute this model are sparse or non‐existent.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…; Gregory et al . ) is generally consistent with the plausibility of KTW dynamics, but observations of complex, natural communities that may support or refute this model are sparse or non‐existent.…”
Section: Discussionsupporting
confidence: 54%
“…; Gregory et al . ), so viruses likely have some impact at the broader ecotype or genus level. Similarly, the discovery of a new family of viruses ( Autolykiviridae ) with broad inter‐species host ranges (Kauffman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Determination of fitness-conferring infection traits for the large collections of closely related phages (e.g., Pope et al, 2015; Gregory et al, 2016; Marston and Martiny, 2016) is a valuable metric that—while labor intensive to collect—would further test this OTU-defining model and enable the application of theory to advance viral community ecology.…”
Section: Resultsmentioning
confidence: 99%
“…These combined trait-based and comparative genomics analyses allowed us to test the validity of proposed sequence-based virus population delineations described above (Brum et al, 2015; Gregory et al, 2016). To do so, we considered Pseudoalteromonas hosts as viral niches and measured infection traits indicative of viral fitness in each niche.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced a methodology that uses genome sequences to delineate reproductively isolated groups within bacteria and archaea based on their barriers of gene exchange, thereby offering a single framework to define biological species for any set of recombining organisms (21). Similarly, viruses do not rely on sexual reproduction; however, recent analyses of homologous recombination and network reconstructions suggest that species delineation based on gene flow would be possible for bacteriophages infecting cyanobacteria (22)(23)(24)(25)(26). Moreover, an experimental evolution study has shown that the mechanisms of…”
mentioning
confidence: 99%